GREEN ECONOMY AND INNOVATION: INTEGRATING ENVIRONMENTAL ACCOUNTING WITH TECHNOLOGICAL ADVANCES IN HEALTHCARE AND INDUSTRY - Meikhati, Ety; Suhatmi, Erna Chotidjah; Ali, Nor Aishah Mohd (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
The Shift toward a green economy has emerged as a global priority in tackling climate change, resource scarcity, and the growing demand for sustainable development. Alongside this transition, rapid progress in healthcare and industrial technologies offers opportunities to boot efficiency, lower emissions, and generate added value. This study explores how green economy principles, environmental accounting, and technological innovation can be integrated within the healthcare and industrial sectors. A qualitative descriptive approach is applied, utilizing literature reviews and document analysis from scientific articles, sustainability reports, and policy documents published in the past five years. The results suggest that combining environmental accounting with technological innovation enhances the realization of a green economy by improving resource efficiency, increasing transparency in sustainability reporting, and supporting the achievement of the Sustainable Development Goals (SDGs). The findings also emphasize the essential function of environmental accounting in measuring the economic impact of technological innovations, particularly in healthcare and industry, which are among the largest contributors to energy use and carbon emissions.